Development of Interactive Learning Application “Smart Educa” as Learning Media for Introductory Business Courses - Umatin, Choiru; Heri Pratikto; Wening Patmi Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to develop an interactive learning application based on Android and Desktop